AN ANALYSIS OF ENGLISH PHRASAL VERB TYPES FOUND IN MAROON 5’S ALBUM SONG ABOUT JANE (2002) AND THEIR TRANSLATION TECHNIQUES - S.Y, Annisa; Nurlaila, Nurlaila (Universitas Gunadarma, 2019)
Phrasal verb is combination of a verb and a preposition or an adverb that is used together and creates a new meaning. The aim of the research is to find out types of English phrasal verb that are used in maroon 5’s album Song About Jane (2002), to find out types of English phrasal verb that are used the most frequently and to find out translation techniques that are applied in translating English phrasal verb in Maroon 5’s album Song About Jane (2002) in English-Indonesian version. The data that is used is the words that contain phrasal verb in lyrics song and the source of data is Maroon 5’s Album Song About Jane (2002). This research is descriptive qualitative. This qualitative research uses expert validation to check the validity of the data and research results. The researcher identifies the data of phrasal verb based on King and Richard’s theory (2006) and identifies the translation techniques that are used based on Molina and Albir’s theory (2002). The results of the research show that there are three (3) types of phrasal verb that are found in Maron 5’s Album Song About Jane (2002), those are : separable obligatory phrasal verb 26% (10 of 38), inseparable phrasal verb 34% (13 of 38) and intransitive phrasal verb 40% (15 of 38), type of English phrasal verb that are used the most frequently in Maroon 5’s album Song About Jane (2002) is intransitive phrasal verb with 15 data, and there are 3 techniques that are used in translating english phrasal verb in maroon 5’s album Song About Jane (2002), those are : generalization 87% (33 of 38), established equivalent 10% ( 4 of 38)and discursive creation 3% (1 of 38).